Characterization of virulence genes cagA and vacA in Helicobacter Pylori and their prevalence in gastrointestinal disorders - Cogo,Laura Lúcia (2011)
Prevalence of H. pylori infection was determined using cultures of gastric biopsy samples of patients attended at the academic hospital of the Federal University of Paraná, Curitiba, Paraná, Brazil. Molecular methods were used to characterize the cagA and vacA genes from bacterial isolates associated with different diseases presented by patients. Out of a total of 81, forty-two gastric biopsy samples tested were positive for H. pylori, with a prevalence of 51.9%. No significant difference was found with regard to the gender (p=0.793) and age (p=0.183) of the patients. Genotype s1m1 vacA gene was found in 67% of the cases of peptic ulcer investigated (p=1.0), despite the limited number of patients with this disease (n=3). A correlation between the presence of less virulent strains (s2m2) and reflux esophagitis was found in the majority of the cases (45%), but without statistical significance. An association between the prevalence of cagA gene, found in 92% of isolates, and peptic ulcer was not observed (p=1.0), suggesting that this gene cannot be considered a specific marker of severity in our environment. The results reinforce the importance of conducting regional studies and the need to characterize H. pylori virulence genes associated with different diseases.